Dysfunctional coronavirus anxiety in nonpsychotic psychiatric outpatients during the COVID‐19 pandemic: A network analysis. Issue 7 (28th March 2022) - Kim, Shin Tae; Seo, Jun Ho; Lee, Sangmin; Jeon, Sumoa; Park, Chun Il; Kim, Se Joo; Kang, Jee In
Abstract: Background: The 2019 coronavirus disease (COVID‐19) pandemic has had a profound impact on the mental health of people worldwide. This study examined dysfunctional coronavirus anxiety in nonpsychotic psychiatric outpatients during the pandemic using the coronavirus anxiety scale (CAS) and examined the relationship between coronavirus anxiety and clinical symptoms using network analysis. Methods: In this cross‐sectional study, 192 patients who first visited the psychiatric outpatient clinic of Severance Hospital during the COVID‐19 pandemic with chief complaints of depressed mood, anxiety, somatic symptoms, or insomnia were included. We compared the clinical characteristics of patients with and without dysfunctional coronavirus anxiety. Network analysis was conducted to estimate the network of coronavirus anxiety and depressive, anxious, and hypochondriacal psychopathology. Results: The results showed that 7.8% of patients exhibited dysfunctional coronavirus anxiety (CAS ≥ 5). Patients with dysfunctional coronavirus anxiety showed higher levels of health worry, somatic preoccupation, and subjective anxiety compared to patients without dysfunctional coronavirus anxiety. In the network analysis, the health worry node (Item 6 of the WI) showed the greatest number of connections with coronavirus anxiety nodes. Conclusions: These findings suggest that health worry may be an important bridge symptom that connects coronavirus anxiety and other clinical psychopathology. Patients with elevated health worries should be carefully monitored during the COVID‐19 pandemic for exacerbation of previous symptoms and COVID‐19‐related psychopathology. Understanding the psychological factors in the face of the pandemic and their relationships with clinical psychiatric symptoms would help people prevent and overcome mental health problems during the pandemic.